Respuesta :
Answer:
[tex]\frac{60x^{20}y^{24}}{30x^{10}y^{12}}[/tex] in simplest form would be [tex]2x^{10}y^{12}.[/tex]
Step-by-step explanation:
Given expression [tex]\frac{60x^{20}y^{24}}{30x^{10}y^{12}}[/tex].
Let us simplify given rational expression in smaller parts.
[tex]\frac{60}{30} = 2[/tex]
[tex]\frac{x^{20}}{x^{10}} = x^{20-10} = x^{10}[/tex]
[tex]\frac{y^{24}}{y^{12}} = y^{24-12} = y^{12}.[/tex]
Combining all terms together, we get
[tex]2x^{10}y^{12}.[/tex]
Therefore,
[tex]\frac{60x^{20}y^{24}}{30x^{10}y^{12}}[/tex] in simplest form would be [tex]2x^{10}y^{12}.[/tex]